Reinterpreting Surah Al-Fatihah through Mohamed Arkoun's Deconstructive Hermeneutics: A Historical-Critical and Linguistic-Semiotic Analysis - Bahri, Samsul; Hidayat, Fairuz (Program Studi Ilmu Al-Qur'an dan Tafsir Fakultas Ushuluddin dan Filsafat, UIN Ar-Raniry, 2026)
The application of deconstructive hermeneutics to the Qur'an remains methodologically and epistemologically contested, particularly when applied to Surah Al-Fatihah, one of the Qur'an's most central liturgical and theological texts. Previous studies have primarily described Mohamed Arkoun's hermeneutical thought without critically examining the internal consistency of his interpretive method or evaluating its relevance and limitations for contemporary Qur'anic studies. This study addresses three questions: why Arkoun selected Surah Al-Fatihah as the object of his analysis, how he operationalized deconstructive hermeneutics in interpreting the surah, and how far this approach is relevant and where its limitations lie for contemporary exegetical scholarship. Employing qualitative library research, the study integrates historical-critical and linguistic-semiotic approaches through a systematic analytical procedure. The findings demonstrate that Arkoun broadens the horizon of Qur'anic interpretation by integrating historical inquiry, linguistic analysis, and critical reflection. Nevertheless, his interpretation relies more heavily on linguistic description than on a systematic semiotic procedure, resulting in methodological inconsistencies and insufficient support for several claims concerning interpretive plurality and the normative authority of the Qur'anic text. The study concludes that Arkoun's hermeneutics offers a valuable critical framework for contemporary Qur'anic studies, provided that its application is accompanied by explicit methodological procedures and normative safeguards to preserve analytical rigor without collapsing into interpretive relativism.